Suriname : 2009 Article IV Consultation-Staff Report; Statement by the Staff Representative; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director. (IMF Staff Country Reports; Country Report, 2010)
This 2009 Article IV Consultation highlights that economic activity weakened in Suriname in 2009 in the context of lower alumina and oil prices and a sharp output decline in the alumina sector. However, economic growth is estimated to have remained positive at 2.5 percent, supported by buoyant activity in the gold and construction sectors. Inflation has fallen sharply. Executive Directors have welcomed the authorities' decision to postpone the reduction in the corporate tax rate, as this would adversely affect tax collections.